2008
DOI: 10.1002/chem.200800815
|View full text |Cite
|
Sign up to set email alerts
|

A General Synthetic Route to Mixed NHC–Phosphane Palladium(0) Complexes (NHC=N‐Heterocyclic Carbene)

Abstract: Mixed NHC-phosphane palladium(0) complexes [(NHC)Pd(PR(3))] (NHC: N-heterocyclic carbene) are synthesized directly from commercially available reagents, with the possibility to tune the nature of both the NHC and the phosphane. Reaction of [(NHC)Pd(allyl)Cl] (palladium source) and PR(3), in the presence of a base afforded, in isopropanol, [(NHC)Pd(PR(3))] in good yields. We found that the nature of the solvent played a key role in the efficient reduction of the Pd(II) precursor to Pd(0). Supported by experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 36 publications
(5 reference statements)
4
74
0
Order By: Relevance
“…[Pd(IPr)(L)] (L = PPh 3 , PCy 3 , IPr), [13] [Pd(SIPr)(PCy 3 )] [13] and [Pd-(PCy 3 ) 2 ] [26] were synthesized according to literature procedures. Anhydrous solvents were purchased from Aldrich and used as received unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Pd(IPr)(L)] (L = PPh 3 , PCy 3 , IPr), [13] [Pd(SIPr)(PCy 3 )] [13] and [Pd-(PCy 3 ) 2 ] [26] were synthesized according to literature procedures. Anhydrous solvents were purchased from Aldrich and used as received unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
“…[11] As part of our investigations on the use of N-heterocyclic carbenes (NHCs) as stabilizing ligands, [12] a synthetic strategy leading to 14-electron Pd 0 complexes was developed. [13] One of these complexes, [Pd(SIPr)(PCy 3 )] (SIPr = N,N'-bis(2,6-(diisopropyl)phenyl)imidazolin-2-ylidine), was successfully used to promote hydrogenation reactions under very mild reaction conditions. [14] During these catalytic studies, the stability of [Pd(SIPr)(PCy 3 )] under hydrogenation conditions was investigated, and NMR spectroscopic studies indicated the presence of a hydride complex which may have resulted from an oxidative addition of H 2 on [Pd(SIPr)(PCy 3 )].…”
mentioning
confidence: 99%
“…263 The same group later developed a methodology for the reduction/trapping of Pd(II) complexes into the carbene-phosphine mixed Pd(0) species in isopropanol, the latter playing the role of a reducing agent via the isopropoxide anion. 259 Considering the advantages of isopropanol, it was therefore chosen as an additive. The ratio 9:1 (H 2 O:i PrOH) was chosen for testing the palladium catalysts.…”
Section: Selection Of An Adequate Complexmentioning
confidence: 99%
“…A catalytic amount of KOt-Bu (10 mol%) in combination with K3PO4 gave a lower yield than the one molar amount (Entry 11 vs. 12). The high activity for the Suzuki-Miyaura cross coupling of some catalysts in isopropanol with a base, it has been attributed to the reduction of the palladium complex by the isopropoxide formed from the reaction between the alcohol and a base [27]. Interestingly, ethanol and methanol gave lower yields, which may indicate that ethoxide and methoxide ions, formed from the reaction between the solvent and the base, are less efficient in reducing the palladium complex than KOt-Bu (Entries 9 and 10 vs. 12).…”
Section: Resultsmentioning
confidence: 99%